Framing Intellectual and Lived Spaces in Early South Asia : Sources and Boundaries. - den Boer, Lucas; Cecil, Elizabeth A. (Berlin/Boston : Walter de Gruyter GmbH, 2020)
Beyond Boundaries: Religion, Region, Language and the State is a research initiative hosted by the British Museum and the British Library in London. Moving beyond geographical, chronological, disciplinary and historiographical boundaries, the books in this series explore the interactions of India and her neighbors from late antiquity to the close of the medieval.
Intro -- Preface -- Contents -- Introduction -- Part I: Text, Image &amp -- amp -- Lived Spaces -- 1. The Enigma of the Centauress and Her Lover: Investigating a Fifth-century Terracotta Panel from Ahichhatrā -- 2. Visual Story-Telling in Text and Image: The Nāga as Inhabitant of the Cosmic Ocean and the Netherworld -- 3. Vyoman: The Sky is the Limit. On the Bhaviṣyapurāṇa's Reworking of the Liṅgodbhava Myth -- 4. Bronze Temple Bells from the Tibetan Imperial Period: Buddhist Material Culture in Context -- Part II: Philosophy &amp -- amp -- Intellectual Spaces -- 5. Nonagonistic Discourse in the Early History of Indian Philosophical Debates: From Brahmodyas to the Mahābhāṣya -- 6. The Legitimation of an Authoritative Discourse in Jainism -- 7. Clay Pots, Golden Rings, and Clean Upper Garments: Causality in Jaina Philosophy -- 8. Charting the Geographies of 'Ju Mi pham rnam rgyal rgya mtsho's Perspectivist Approach to the Two Truths -- List of Contributors -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books